2016
DOI: 10.1021/acs.joc.6b02390
|View full text |Cite
|
Sign up to set email alerts
|

The Logic behind a Physical–Organic Chemist’s Research Topics

Abstract: Abstract. Although my research has no common theme or defining area, a coherence connects the diverse topics, insofar as one project leads logically to another. Thus studies on mechanisms of hydrogen exchange in amides and amidines led to the influence of hydrogenbonding and to NMR methods for chemical kinetics, including 2D-EXSY spectroscopy.Another connection was the OH --catalyzed NH exchange in amines that had supported the hypothesis of stereoelectronic control. We therefore analyzed that hypothesis criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 154 publications
0
9
0
Order By: Relevance
“…The inverse 2°N-CH 3 /CD 3 EIEs (0.91−0.81) for the conversion from MAH/DMAH/DMPBIH to MA + / DMA + /DMPBI + are consistent with the "negative hyperconjugative effect" explanation, which uses the concept that the CD 3 -N base is stronger than the CH 3 -N base (Table 1). 35,36 The 10-N-CH 3 /CD 3 EIE on the conversion from MAH to MA + (0.883) is more inverse than that from DMAH to DMA + (0.905) (Table 1). This can be interpreted in terms of more electron density localized on N in MAH available for the negative hyperconjugative effect (due to less planar sp 2.31 hybridization) than in DMAH (more planar with sp 2.07 hybridization) (Table 3).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse 2°N-CH 3 /CD 3 EIEs (0.91−0.81) for the conversion from MAH/DMAH/DMPBIH to MA + / DMA + /DMPBI + are consistent with the "negative hyperconjugative effect" explanation, which uses the concept that the CD 3 -N base is stronger than the CH 3 -N base (Table 1). 35,36 The 10-N-CH 3 /CD 3 EIE on the conversion from MAH to MA + (0.883) is more inverse than that from DMAH to DMA + (0.905) (Table 1). This can be interpreted in terms of more electron density localized on N in MAH available for the negative hyperconjugative effect (due to less planar sp 2.31 hybridization) than in DMAH (more planar with sp 2.07 hybridization) (Table 3).…”
Section: ■ Discussionmentioning
confidence: 99%
“…It was found that the CD 3 base is stronger than the CH 3 base, leading to EIE < 1. The current explanation uses the concept of negative hyperconjugative effect between the lone pair electrons in sp 3 -hybridized N and the empty σ* orbital of the β-C–L bond. , This effect weakens the C–L bond (via an S N 2-like mechanism, Scheme ). When CL 3 –NR 2 is protonated, forming CL 3 –N + HR 2 , this effect disappears, strengthening the C–L bond and thus resulting in an inverse EIE.…”
Section: Introductionmentioning
confidence: 99%
“…These rather complicated behaviors of amides suggest the existence of multiple proton exchange mechanisms due to the delocalization of the lone electron pair of its nitrogen. [45][46][47][48] Therefore, more reactions should be considered in the extension of the Bloch equations.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphate glass immersed in aqueous solution will generate O − groups at the glass surface due to the rapid release of sodium ions, whilst the CS in low-pH aqueous solution could have generated NH 3 + groups (see Figure 9) [46]. Strong hydrogen bonds of 20-40 kcal/mol could be formed between the charged donor and acceptor groups that are nearly as strong as covalent bonds [48]. Kohl et al [49] reported that glass fibres with native surface hydroxyl groups could have strong hydrogen-bonding interactions (high surface energy) with polar functional groups of the polymers in glass fibre-reinforced composites.…”
Section: Interfacial Propertiesmentioning
confidence: 99%